Diversity in European marketing : Text and cases - Rudolph, Thomas (Gabler Verlag, 2012)
Given its unique heritage and diversity, Europe deserves and requires distinct marketing attention. This book offers a non-traditional perspective to European marketing by addressing up-to-date issues and challenges for marketers through short cases and relevant received theory. Specific student assignments further provide educators, who want to take a European perspective in their teaching, with probing discussion material and encourage readers to think ahead. All cases are written by expert academics of leading management schools in Europe, establishing diversity in culture and approaches. The topics are accordingly as diverse as its contributors and include case studies and insights on the European marketing and management of companies such as Aldi, Delhaize, DeLaval, Deutsche Bank, KFC, Kofola, Puma, and Vestas Wind Systems, among others. Contents Diverse Demographics and Structural Diversity Diversity in Consumer Behavior in Europe Diverse Marketing Environments and Diversity Management Target Groups Bachelor and Master students wanting to pursue a career in marketing and related domains, Managers involved in diverse marketing issues (such as product and brand managers, retail category managers, supply chain managers or communication and public relation experts). About CEMS CEMS (Community of European Management Schools) is a strategic alliance of leading business schools and multinational companies. Its mission is to set a global standard of excellence in education.